Intraoral and extraoral soft tissue lesions and periodontal health in the occupational medical examination of construction workers in Lima, Peru - Manrique-Chávez, Carolina B. (2025)
Objective: To describe intraoral and extraoral soft tissue lesions and periodontal health identified during the occupational medical evaluation of operational and administrative workers in the construction sector of Lima, Peru. Materials and methods: A cross-sectional study conducted on 150 construction workers evaluated with a dental-occupational instrument with epidemiological indices for periodontal disease and clinical attachment loss, as well as indicators for intraoral and extraoral lesions. Results: The community periodontal index of young adult operational workers (bleeding = 3.58; pocket = 1.13) and mature adult operational workers (bleeding = 3.04; pocket = 1.16) was higher than that of young adult administrative workers (bleeding = 1.55; pocket = 0.73) and mature adult administrative workers (bleeding = 1.05; pocket = 0.84). Young adult operational workers (CAL= 36.50%; n = 19) and mature adult operational workers (CAL = 36.77%; n = 27) had a higher frequency of clinical attachment loss than young adult administrative workers (CAL= 18.20%; n = 7) and mature adults (CAL= 15.80%; n = 3). Regarding operational workers, 94.90% (n = 114) had gingivitis and 61.95% (n = 74) suffered from periodontitis. In addition, they showed a higher frequency of intraoral lesions (63.30% [n = 95] vs. 6.00% [n = 9]) and extraoral lesions (55.30% [n = 83] vs. 11.30% [n = 17]) compared to administrative workers. Conclusions: Periodontal health, clinical attachment, and intraoral and extraoral conditions of operational construction workers are significantly more impaired than those of administrative workers.